Phoneme-based or isolated-word modeling speech recognition system? An overview - Yusnita, M. A.; Murugesa Pandiyan, Paulraj, Assoc. Prof. Dr.; Sazali, Yaacob, Prof. Dr.; Shahriman, Abu Bakar; Saidatul Ardeenaawatie, Awang; Ahmad Nazri, Abdullah (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/